Faktor-Faktor yang Mempengaruhi Tingkat Pengungkapan Wajib LKPD Kabupaten/Kota di Kalimantan Selatan - Shindy Putri Pramesti; Alfian Misran (Jurnal Eksplorasi Akuntansi, 2021)
This study tested and proved the effect of intergovernmental revenue, regional wealth, regional expenditure, and human development index on the level of mandatory disclosure of local government financial statements in South kalimantan. The independent variables in this study is intergovernmental revenue, regional wealth, regional expenditure, and human development index. Meanwhile, the dependent variable in this study is level of mandatory disclosure of local government financial statements. Population of this research covers 13 districts and cities within South Kalimantan in the period 2015-2018. The sample was selected using purposive sampling method and obtain of 52 local government financial statements. The analysis technique used on this study is multiple linear regression by SPSS 25 program. The result showed the variable intergovernmental revenue have effect on the level of mandatory disclosure. Variable regional wealth, regional expenditure and human development index do not have effect on the level of mandatory disclosure. This study also indicate that average of mandatory disclosure in South Kalimantan province is 77,98%.